(untitled) (Asian Journal of Medical Research and Health Sciences, 2026)
Objective: To study the association between text neck pain and level of neck disability in relation to duration of digital gadgets usage among university students. Study Design: cross-sectional study Material and Methods: This study was conducted on university students with ages 18 and above. The data was collected from University of Child Health Sciences, Children’s Hospital Lahore (UCHS) and Pakistan Society for Rehabilitation of Differently Abled (PSRD). 382 students participated in this study. Questionnaire was provided to students who met inclusion criteria after informed consent. Results: Out of 382 students, 82.5% were female and 17.5% were male. The majority of the participants were first year students (39.3%). More than half (50.5%) used digital gadgets an average of 4-6 hours a day, and 23.3% used them an average of 7-9 hours a day. Most people (55.5%) took a moderately flexed position with their necks, while only 1.3% assumed a neutral position. For neck disability, 51.6% had mild, 26.7% had no, 17.3% had moderate and 4.4% had severe disability. A quarter of the previous year (25.4%) had neck problems for 8-30 days during the past year. There were significant correlations between neck disability severity and the duration of neck trouble, and between the duration of using digital gadgets and the severity of neck disability and the duration of neck trouble (p < 0.001). Conclusion: It was concluded that the excessive usage of digital gadgets significantly impacts the duration of neck trouble and level of neck disability.